All-terrain vehicle use: A value-norm-perception model predicting perceived impact on coastal dunes. (September 2021) - Hogan, Jessica L.; Sponarski, Carly C.; Vaske, Jerry J.
Abstract: Coastal dunes are sensitive to human pressure, even at low use levels. With the increase of all-terrain vehicle (ATV) use on dunes and the impacts associated with trampling dune vegetation, ATVs have become a primary concern for land managers charged with coastal protection. To better understand the situation, this article examined the relationships among ATV users': (a) general value orientations (i.e., mutualism and domination, (b) norms (i.e., Awareness of Consequences, AC, and Ascription of Responsibility, AR), and (c) perceived impacts on coastal sand dunes. The two norms constructs were predicted to mediate the relationship between general value orientations and perceived impacts. Data were obtained from a systematic random sample of ATV users in the three communities in rural Canada ( n  = 97). Results indicated that mutualism was positively related to AC and AR and domination was negatively related to AC. Domination and AC were related to perceived impacts on coastal sand dunes. None of the other predicted relationships, however, were statistically significant. Management Implications: All-terrain vehicles (ATV) users generally agreed with mutualism, awareness of consequences (AC), and ascription of responsibility (AR) suggesting support may exist to preserve dunes. Managers should incorporate mutualism and AC into their messages to influence perceptions of impact. As domination had a negative (AC, perceived impacts) or no relationship (AR) to constructs, awareness initiatives about ATV impacts may be important.